Penerapan Contextual Learning untuk Meningkatkan Hasil Belajar IPAS Siswa Kelas V Sekolah Dasar - Wardah Putri Fa’izah; Nur Azizah; Aulia Riana; Desi Eka Pratiwi (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
IPAS is a subject that must be given to elementary school students. However, several studies show that elementary school students' learning outcomes in IPAS subjects are still low. This research aims to determine the effect of implementing the contextual teaching and learning model on IPAS. This research was carried out at SDN Pakis V in the 2024 academic year with a sample of class VC students. SDN Pakis V as many as 30 children. Data collection in this research used test techniques with questions in the form of descriptions. From this research, it was found that student learning results showed improvement after learning using the contextual teaching and learning model, with an average pre-test result of 70.86 while the post-test result was 85.56. The results of hypothesis testing with the t-test also show that there is a difference in the average test results before and after implementing the contextual teaching and learning model. With these results, the conclusion of this research is that the Contextual Teaching and Learning Model can improve students' IPAS outcomes in Class V at SDN Pakis V.